Energy storage battery cell and preparation method thereof

By introducing molybdenum-based bismuth acid into the lithium manganate positive electrode material, its shortcomings in high temperature adaptability and cycling performance are solved, and higher battery performance is achieved.

CN118867409BActive Publication Date: 2025-02-07ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411370576.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Lithium manganate positive electrode material has shortcomings in high temperature adaptability and cycling performance, which limits its wide application in electric vehicles and other fields.

Method used

By preparing a mixed solution containing lithium manganese oxide, bismuth salt and molybdenum-based acid salt, and undergoing solvothermal reaction treatment, bismuth molybdenum-based acid is generated and the positive electrode material is modified.

Benefits of technology

The modified cathode material exhibits excellent oxidation resistance and structural stability at high temperatures, significantly improving its cycling and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867409B_ABST
    Figure CN118867409B_ABST
Patent Text Reader

Abstract

The present application relates to the field of energy storage technology, and in particular to energy storage cells and preparation methods thereof, wherein the preparation method of the energy storage cell includes preparing a positive electrode material, and the steps of preparing the positive electrode material include: preparing a mixed solution containing lithium manganate, bismuth salt and molybdate acid salt, wherein the molybdate acid salt includes at least one of molybdate, tungstate and vanadate, wherein the molar amount of bismuth ions in the mixed solution is n1, the total molar amount of molybdate ions, tungstate ions and vanadate ions is n2, and the molar amount of lithium manganate is n3, n1:n2:n3=(1.05~2.2):1:(100~200); the mixed solution is subjected to solvent thermal reaction treatment to obtain a positive electrode material. The technical solution of the present application uses molybdate acid salt and bismuth salt to modify the lithium manganate positive electrode material, so that the high temperature adaptability and cycle performance of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to an energy storage battery cell and a preparation method thereof. Background Art

[0002] Lithium-ion batteries dominate the global secondary battery market with their advantages such as high operating voltage, wide operating range, high specific energy, no pollution and long service life. Especially in recent years, they have been widely used in fields such as electric vehicles.

[0003] From the composition of lithium-ion batteries, the positive electrode material accounts for a large proportion, about 3-4 times that of the negative electrode material. It can be seen that the performance of the positive electrode material directly affects the performance of the battery. x Co y Mn 1-x-y Positive electrode materials such as O2 have been widely studied, but the lithium-ion battery systems assembled with these positive electrode materials have defects such as high cost and poor safety.

[0004] Lithium manganese oxide has the huge advantages of low price, abundant mineral reserves and strong safety, and its comprehensive performance is much better than lithium cobalt oxide and ternary materials. However, there are still some problems in its high temperature adaptability and cycle performance, which greatly limits its application. Summary of the invention

[0005] The present application provides an energy storage battery cell and a preparation method thereof, which can improve the high temperature adaptability and cycle performance of lithium manganese oxide positive electrode materials, thereby improving the high temperature adaptability and cycle performance of the energy storage battery cell.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing an energy storage battery cell, including preparing a positive electrode material, wherein the steps of preparing the positive electrode material include:

[0007] A mixed solution containing lithium manganate, bismuth salt and molybdate acid salt is prepared, wherein the molybdate acid salt includes at least one of molybdate, tungstate and vanadate, wherein the molar amount of bismuth ions in the mixed solution is n1, the total molar amount of molybdate ions, tungstate ions and vanadate ions is n2, the molar amount of lithium manganate is n3, and n1:n2:n3=(1.05-2.2):1:(100-200);

[0008] The mixed solution is subjected to a solvothermal reaction treatment to obtain a positive electrode material.

[0009] In some embodiments, the mixed solution further contains bismuth oxide, and the molar amount of bismuth oxide in the mixed solution is n4, n4:n2=(0.1~0.2):1.

[0010] In some embodiments, the temperature of the solvothermal reaction treatment is 140° C. to 200° C., and the time of the solvothermal reaction treatment is 12 h to 24 h.

[0011] In some embodiments, the mixed solution further contains 1 mmol to 2 mmol of a surfactant, and the surfactant is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and hexadecylpentyldimethylammonium bromide.

[0012] In some embodiments, the pH of the mixed solution is 1-5.

[0013] In some embodiments, the preparation of a mixed solution containing lithium manganate, bismuth salt and molybdenum acid salt comprises the steps of: uniformly mixing the bismuth salt solution, the molybdenum acid salt solution and the lithium manganate;

[0014] Before the bismuth salt solution, the molybdate acid salt solution and the lithium manganate are uniformly mixed, the preparation method further comprises the following steps:

[0015] Preparation of the lithium manganate: uniformly mixing a lithium source and a manganese source, wherein the molar ratio of lithium ions in the lithium source to manganese ions in the manganese source is (1-1.2):3, to obtain a manganese-lithium mixture, and then calcining the manganese-lithium mixture at 750° C. to 900° C. to obtain lithium manganate; and / or,

[0016] preparing the bismuth salt solution: mixing a bismuth source with a first solvent to prepare a first prepared solution, adding a surfactant and bismuth oxide to the first prepared solution to obtain a bismuth salt solution; and / or,

[0017] The molybdenum acid salt solution is prepared by mixing a molybdenum source with a second solvent to prepare a second prepared solution, wherein the molybdenum source includes at least one of a molybdenum source, a tungsten source and a vanadium source, to obtain a molybdenum acid salt solution.

[0018] In some embodiments, after adding a surfactant and bismuth oxide to the first prepared solution, the preparation method further comprises adjusting the first prepared solution to be acidic.

[0019] In some embodiments, the bismuth source includes bismuth nitrate pentahydrate.

[0020] In some embodiments, after the molybdenum-based source and the second solvent are mixed to form a second prepared solution, the preparation method further comprises adjusting the second prepared solution to be acidic.

[0021] In some embodiments, the molybdenum source includes sodium molybdate dihydrate.

[0022] In some embodiments, the tungsten source includes sodium tungstate dihydrate.

[0023] In some embodiments, the vanadium source comprises sodium vanadate.

[0024] In some embodiments, the first solvent and the second solvent are independently selected from at least one of water, ethanol, and ethylene glycol.

[0025] In some embodiments, the concentration of the first prepared solution and / or the second prepared solution is ≥ 0.1 mol / L.

[0026] In a second aspect, the present application also provides an energy storage battery cell, which is prepared by the preparation method described in the first aspect, wherein the energy storage battery cell comprises a positive electrode sheet coated with a positive electrode material, wherein the positive electrode material comprises a lithium manganese oxide substrate, and Bi in-situ grown on the lithium manganese oxide substrate. x M y O z , wherein x, y, z>0, and M includes at least one of molybdenum, tungsten and vanadium;

[0027] In the positive electrode material, the molar amount of lithium manganate matrix is ​​n3, Bi x M y O z The molar amount of element M is n2, n2:n3=1:(100~200).

[0028] In some embodiments, in the positive electrode material, the Bi element partially combines with the acid radical ion of the M element to form Bi x-m M y O z , and the other part is deposited on Bi x-m M y O z Above, 0<m<x.

[0029] In some embodiments, in the positive electrode material, Bi x-m M y O z The molar mass is n5, deposited on Bi x-m M y O z The molar amount of Bi element is n6, n6:n5=(0.1~0.2):1.

[0030] Compared with the prior art, this technical solution has at least the following technical effects:

[0031] The technical solution of this application uses molybdenum acid salts and bismuth salts to modify the lithium manganese oxide positive electrode material, so that the high temperature adaptability and cycle performance of the positive electrode material are improved. In the solvent thermal reaction treatment, the bismuth salt and molybdenum acid salt in the mixed solution will generate an appropriate amount of molybdenum acid bismuth (bismuth molybdate, bismuth tungstate and bismuth vanadate) in situ on the surface of lithium manganese oxide. Since the molybdenum acid bismuth (bismuth molybdate, bismuth tungstate and bismuth vanadate) compounds belong to Aurivillius compounds, they have excellent high temperature oxidation resistance and structural stability. The appropriate amount of molybdenum acid bismuth is compounded with lithium manganese oxide to improve the high temperature performance and cycle performance of the lithium manganese oxide positive electrode material; in addition, since bismuth molybdate is a semiconductor photocatalyst with excellent performance and a suitable bandgap width, it is conducive to the separation of electron-hole pairs. By compounding it with lithium manganese oxide, it is beneficial to improve the electron mobility of the positive electrode material, thereby improving the rate performance of the positive electrode material. In addition, the improved cycle performance of the modified lithium manganese oxide positive electrode material is also attributed to the unique morphology of bismuth molybdenum acid. Specifically, since bismuth molybdenum acid is in the form of particles with a particle size smaller than that of lithium manganese oxide, it is easy to insert between lithium manganese oxide particles. Moreover, since bismuth molybdenum acid is in the form of flower-like microspheres with wrinkles / pores on its surface, it can be tightly combined with lithium manganese oxide particles, which can not only improve the overall compaction density of the positive electrode material, but also improve the structural stability of the positive electrode material, thereby further improving the cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0033] Figure 1 A schematic diagram of a process for preparing an energy storage cell according to an embodiment of the present application;

[0034] Figure 2 A schematic diagram of the preparation process of the positive electrode material in one embodiment of the present application;

[0035] Figure 3 Schematic diagram of the preparation process of the positive electrode material in another embodiment of the present application. DETAILED DESCRIPTION

[0036] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0037] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0040] In a first aspect, an embodiment of the present application provides a method for preparing an energy storage cell.

[0041] See also Figure 1 In the embodiment of the present application, the preparation method of the energy storage cell comprises the following steps:

[0042] S100. Preparing positive electrode materials and negative electrode materials;

[0043] S200. Coating the positive electrode material on the positive electrode collector and rolling to obtain a positive electrode sheet;

[0044] S300. Coating the negative electrode material on the negative electrode current collector and rolling to obtain a negative electrode sheet;

[0045] S400. Wind the positive electrode sheet, the negative electrode sheet and the separator to obtain an energy storage cell.

[0046] See also Figure 2 In the embodiment of the present application, the steps of preparing the positive electrode material include:

[0047] S110. Prepare a mixed solution containing lithium manganate, bismuth salt and molybdate acid salt, wherein the molybdate acid salt includes at least one of molybdate, tungstate and vanadate, wherein the molar amount of bismuth ions in the mixed solution is n1, the total molar amount of molybdate ions, tungstate ions and vanadate ions is n2, the molar amount of lithium manganate is n3, and n1:n2:n3=(1.05~2.2):1:(100~200);

[0048] S120. Performing a solvent thermal reaction treatment on the mixed solution to obtain a positive electrode material.

[0049] The technical solution of this application uses molybdenum acid salts and bismuth salts to modify the lithium manganese oxide positive electrode material, so that the high temperature adaptability and cycle performance of the positive electrode material are improved. In the solvent thermal reaction treatment, the bismuth salt and molybdenum acid salt in the mixed solution will generate an appropriate amount of molybdenum acid bismuth (bismuth molybdate, bismuth tungstate and bismuth vanadate) in situ on the surface of lithium manganese oxide.

[0050] Since bismuth molybdate (bismuth molybdate, bismuth tungstate and bismuth vanadate) compounds belong to Aurivillius compounds, they have excellent high-temperature oxidation resistance and structural stability. Compounding an appropriate amount of bismuth molybdate with lithium manganate can improve the high-temperature performance and cycle performance of lithium manganate positive electrode materials. In addition, since bismuth molybdate is a semiconductor photocatalyst with excellent performance and a suitable bandgap width, it is beneficial to the separation of electron-hole pairs. By compounding it with lithium manganate, it is beneficial to improve the electron mobility of the positive electrode material, thereby improving the rate performance of the positive electrode material.

[0051] In addition, the improved cycle performance of the modified lithium manganese oxide positive electrode material is also attributed to the unique morphology of bismuth molybdenum acid. Specifically, since bismuth molybdenum acid is in the form of particles with a particle size smaller than that of lithium manganese oxide, it is easy to insert between lithium manganese oxide particles. Moreover, since bismuth molybdenum acid is in the form of flower-like microspheres with wrinkles / pores on its surface, it can be tightly combined with lithium manganese oxide particles, which can not only improve the overall compaction density of the positive electrode material, but also improve the structural stability of the positive electrode material, thereby further improving the cycle performance of the positive electrode material.

[0052] In the embodiment of the present application, preferably, the molybdenum acid salt is molybdate. Compared with bismuth tungstate and bismuth vanadate, bismuth molybdate has more wrinkles / pores on its surface, and has a higher degree of bonding with lithium manganate particles, which is more conducive to improving the compaction density and structural stability of the positive electrode material.

[0053] The preparation method provided in the examples of the present application is described in detail below:

[0054] S110. Prepare a mixed solution containing lithium manganese oxide, bismuth salt and molybdate acid salt, the molybdate acid salt includes at least one of molybdate, tungstate and vanadate. In the mixed solution, the molar amount of bismuth ions is n1, the total molar amount of molybdate ions, tungstate ions and vanadate ions is n2, the molar amount of lithium manganese oxide is n3, n1:n2:n3=(1.05~2.2):1:(100~200).

[0055] In the embodiments of the present application, the ratio of n1 to n2 can be 1.05:1, 1.3:1, 1.6:1, 1.9:1, 2.2:1 or any value therebetween. In some embodiments, the ratio of n1 to n2 is (1.05-1.2):1, (2.05-2.1):1, (2.1-2.15):1 or (2.15-2.2):1.

[0056] In the embodiment of the present application, the ratio of n2 to n3 can be 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190, 1:200 or any value therebetween. In some embodiments, the ratio of n2 to n3 is 1:(100-120), 1:(120-150), 1:(150-180) or 1:(180-200).

[0057] In step S110, the molar ratio of bismuth salt, molybdenum acid salt and lithium manganese oxide in the prepared mixed solution is controlled within an appropriate range, so that the content of bismuth molybdenum acid generated in situ on the surface of lithium manganese oxide is within an appropriate range. If the content of bismuth molybdenum acid is too low, it is difficult to effectively improve the high temperature performance and cycle performance of the positive electrode material. If the content of bismuth molybdenum acid is too high, it will have an adverse effect on the electrochemical properties of the positive electrode material.

[0058] See also Figure 3 In the embodiment of the present application, further, the mixed solution also contains bismuth oxide, and the molar amount of bismuth oxide in the mixed solution is n4, n4:n2=(0.1~0.2):1, specifically, the ratio of n4 to n2 can be 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1, 0.2:1 or any value therebetween.

[0059] During the solvent thermal reaction treatment, the bismuth atoms provided by bismuth oxide will be deposited on the bismuth molybdate acid that grows in situ on the surface of lithium manganese oxide. Bismuth oxide is of the same series as bismuth nitrate and bismuth molybdate acid. On the one hand, it can improve the conversion rate of bismuth nitrate, that is, the generation of bismuth molybdate acid on the surface of lithium manganese oxide is more complete; on the other hand, it can improve the purity and structural stability of the positive electrode material: because the bismuth atoms provided by bismuth oxide are of the same series as bismuth molybdate acid, they are more likely to occupy vacancies on the surface of bismuth molybdate, so that there are fewer impurities on the surface of bismuth molybdate and the purity of the positive electrode material is higher. Moreover, because the bismuth atoms are of the same series as bismuth molybdate, there is an interfacial chemical reaction between the bismuth atoms deposited on bismuth molybdate and bismuth molybdate, which can improve the binding tightness between bismuth molybdate particles, thereby further improving the structural stability of the positive electrode material.

[0060] In the embodiment of the present application, the ratio of n4 to n2 is too high, that is, the content of bismuth oxide in the mixed solution is too high, which is not conducive to the in situ growth of bismuth molybdate on the surface of lithium manganese oxide; the ratio of n4 to n2 is too low, that is, the content of bismuth oxide in the mixed solution is too high, which will result in too few bismuth atoms deposited on the bismuth molybdate, making it difficult to play a modification role.

[0061] In the embodiment of the present application, further, the mixed solution also contains 1 mmol to 2 mmol of a surfactant, specifically, the content of the surfactant in the mixed solution can be 1 mmol, 1.2 mmol, 1.4 mmol, 1.6 mmol, 1.8 mmol, 2 mmol or any value therebetween. By adding an appropriate amount of a surfactant, the morphology of the generated bismuth molybdenum acid can be regulated, so that more wrinkles / pores are generated on the surface of the bismuth molybdenum acid, and the binding tightness of the bismuth molybdenum acid and lithium manganate is further improved.

[0062] Specifically, the surfactant may be selected from one or more of cetyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate (SDBS), and cetylpentyldimethylammonium bromide (DDAC).

[0063] In the embodiment of the present application, the pH of the mixed solution is 1 to 5, specifically 1, 2, 3, 4, 5 or any value therebetween. At this pH, the morphology of the bismuth molybdenum acid in situ generated on the surface of lithium manganese oxide can be better: more wrinkles / pores are generated on the surface of the bismuth molybdenum acid, so that the binding tightness between the bismuth molybdenum acid and lithium manganese oxide is further improved.

[0064] In an embodiment of the present application, preparing a mixed solution containing lithium manganese oxide, bismuth salt and molybdenum acid salt includes the steps of: uniformly mixing the bismuth salt solution, the molybdenum acid salt solution and the lithium manganese oxide.

[0065] In some embodiments, before the bismuth salt solution, the molybdate acid salt solution and the lithium manganate are uniformly mixed, the preparation method further comprises the following steps:

[0066] Preparation of the lithium manganate: uniformly mixing a lithium source and a manganese source, wherein the molar ratio of lithium ions in the lithium source to manganese ions in the manganese source is (1-1.2):3, to obtain a manganese-lithium mixture, and then calcining the manganese-lithium mixture at 750°C-900°C to obtain lithium manganate; wherein the molar ratio of lithium ions in the lithium source to manganese ions in the manganese source can be specifically 1:3, 1.05:3, 1.1:3, 1.15:3, 1.2:3 or any value therebetween, and the specific temperature of the calcination treatment can be 750°C, 800°C, 850°C, 900°C or any value therebetween;

[0067] Preparing a bismuth salt solution: mixing a bismuth source with a first solvent to prepare a first prepared solution, and adding a surfactant and bismuth oxide to the first prepared solution to obtain a bismuth salt solution;

[0068] Prepare a molybdenum acid salt solution: mix a molybdenum source with a second solvent to prepare a second prepared solution, wherein the molybdenum source includes at least one of a molybdenum source, a tungsten source and a vanadium source, to obtain a molybdenum acid salt solution.

[0069] In some embodiments, the molar ratio of lithium ions in the lithium source to manganese ions in the manganese source is (1-1.05):3, (1.05-1.1):3, (1.1-1.15):3 or (1.1-2):3.

[0070] In some embodiments, the calcination temperature may be 750°C to 800°C, 800°C to 850°C, or 850°C to 900°C.

[0071] In some embodiments, after adding the surfactant and bismuth oxide to the first prepared solution, the preparation method further comprises adjusting the first prepared solution to be acidic, specifically adjusting the pH to 1, 2, 3, 4, 5 or any value therebetween.

[0072] In some embodiments, the bismuth source includes bismuth nitrate pentahydrate, and those skilled in the art may also select other bismuth sources according to actual conditions.

[0073] In some embodiments, after mixing the molybdenum source with the second solvent to prepare a second prepared solution, the preparation method further includes adjusting the second prepared solution to be acidic, specifically adjusting the pH to 1, 2, 3, 4, 5 or any value therebetween.

[0074] In some embodiments, the molybdenum source includes sodium molybdate dihydrate, and those skilled in the art may also select other molybdenum sources according to actual conditions.

[0075] In some embodiments, the tungsten source includes sodium tungstate dihydrate, and those skilled in the art may also select other tungsten sources according to actual conditions.

[0076] In some embodiments, the vanadium source includes sodium vanadate, and those skilled in the art may also select other vanadium sources according to actual conditions.

[0077] In some embodiments, the first solvent and the second solvent are independently selected from at least one of water, ethanol and ethylene glycol, and those skilled in the art may make a selection according to actual conditions.

[0078] In some embodiments, the concentration of the first prepared solution and / or the second prepared solution is ≥ 0.1 mol / L. By adjusting the concentrations of the first prepared solution and the second prepared solution to a suitable range, on the one hand, it is convenient to prepare the first prepared solution and the second prepared solution, and on the other hand, it is convenient to perform a subsequent charge-discharge test on the positive electrode material.

[0079] S120. Performing a solvent thermal reaction treatment on the mixed solution to obtain a positive electrode material.

[0080] In some embodiments, the temperature of the solvothermal reaction treatment is 140°C to 200°C, specifically 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or any value therebetween. The temperature of the solvothermal reaction treatment is ≥140°C, which is beneficial to improving the yield of the bismuth molybdate in-situ grown on the surface of the lithium manganese oxide; the temperature of the solvothermal reaction treatment is ≤200°C, which is beneficial to improving the binding tightness between the bismuth atoms provided by bismuth oxide and bismuth molybdate.

[0081] In some embodiments, the temperature of the solvothermal reaction treatment is 140°C to 160°C, 160°C to 170°C, 170°C to 180°C, or 180°C to 200°C.

[0082] In some embodiments, the solvent thermal reaction treatment time is 12 h to 24 h, specifically 12 h, 16 h, 18 h, 20 h, 22 h, 24 h or any value therebetween.

[0083] In some embodiments, the solvothermal reaction treatment time is 12 h to 16 h, 16 h to 18 h, 18 h to 20 h, or 20 to 24 h.

[0084] In the embodiments of the present application, more specifically, after the mixed solution is subjected to a solvent thermal reaction treatment, the preparation method further comprises the step of: purifying the solvent thermal reaction treatment product.

[0085] In some embodiments, the purifying step comprises:

[0086] washing the product of the solvent thermal reaction;

[0087] The washed product is dried.

[0088] In some embodiments, the washing process comprises: centrifuging the product of the solvothermal reaction and washing it alternately with deionized water and anhydrous ethanol.

[0089] In some embodiments, the drying process comprises: drying the washed product in a vacuum drying oven at 60° C. to 80° C. for 6 h to 12 h, and grinding the washed product after cooling.

[0090] S200, coating the positive electrode material on the positive electrode current collector, and rolling to obtain a positive electrode sheet.

[0091] In some embodiments, the positive electrode current collector includes one or more of copper foil, aluminum foil, nickel foil, and a composite current collector.

[0092] In some embodiments, before coating the positive electrode material on the positive electrode current collector, the process further includes: mixing the positive electrode material prepared in S100 with a conductive agent and a binder to obtain a slurry, and then coating the slurry on the positive electrode current collector.

[0093] Optionally, the conductive agent may include at least one of conductive carbon black, flake graphite, graphene or carbon nanotubes.

[0094] Optionally, the binder may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

[0095] In some embodiments, the slurry can be coated on both sides of the positive electrode current collector, and the coating method includes at least one of blade coating, roller transfer coating or slit extrusion coating. During the coating process, it is necessary to control the coating speed, pressure and gap of the coating head to obtain a uniform coating. In some embodiments, the coating speed is greater than or equal to 80 m / min, for example, it can be 80 m / min, 85 m / min, 90 m / min, 100 m / min, 110 m / min or 120 m / min, etc.

[0096] In some embodiments, after coating, the method further includes: drying the wet film obtained by coating to remove water and other volatile components. In some embodiments, the drying equipment may be an oven, for example.

[0097] In some embodiments, the coating result is subjected to roller pressing to obtain a positive electrode sheet. The equipment for roller pressing can be, for example, a roller press, and the coating result can be compacted by the pressure of the roller in the roller press. During the rolling process, the thickness of the electrode sheet will decrease, and the density will increase, thereby improving the density and electrochemical performance of the positive electrode sheet. In some embodiments, the rolling speed is less than or equal to 90 m / min, for example, it can be 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min or 90 m / min, etc. The thickness accuracy of the electrode sheet obtained after rolling is ±3 μm.

[0098] S300, coating the negative electrode material on the negative electrode current collector, and rolling to obtain a negative electrode sheet.

[0099] In some embodiments, the negative electrode material includes a negative electrode active material, a conductive agent, and a binder.

[0100] Optionally, the negative electrode active material includes at least one of soft carbon, hard carbon, artificial graphite, natural graphite, amorphous carbon, silicon oxide or lithium titanate.

[0101] Alternatively, the binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamideimide, polysiloxane, polystyrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin or polyfluorene.

[0102] Optionally, the conductive agent may include at least one of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes or graphene.

[0103] In some embodiments, the negative electrode material can be coated on both sides of the negative electrode current collector, and the coating method includes at least one of blade coating, roller transfer coating or slit extrusion coating. During the coating process, it is necessary to control the coating speed, pressure and gap of the coating head to obtain a uniform coating. In some embodiments, the coating speed is greater than or equal to 80 m / min, for example, it can be 80 m / min, 85 m / min, 90 m / min, 100 m / min, 110 m / min or 120 m / min, etc.

[0104] In some embodiments, after coating, the method further includes: drying the wet film obtained by coating to remove water and other volatile components. In some embodiments, the drying equipment may be an oven, for example.

[0105] In some embodiments, the coating result is subjected to roller pressing to obtain a negative electrode sheet. The equipment for roller pressing can be, for example, a roller press, and the coating result can be compacted by the pressure of the roller in the roller press. During the rolling process, the thickness of the sheet will decrease, and the density will increase, thereby improving the density and electrochemical performance of the negative electrode sheet. In some embodiments, the rolling speed is less than or equal to 90 m / min, for example, it can be 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min or 90 m / min, etc. The thickness accuracy of the sheet obtained after rolling is ±3 μm.

[0106] S400, winding the positive electrode sheet, the negative electrode sheet and the separator to obtain a wound battery cell.

[0107] In some embodiments, before winding, the positive electrode sheet and the negative electrode sheet are cut separately, and the positive electrode sheet and the negative electrode sheet are divided into fixed widths to form the tab state required by the battery structure.

[0108] In this step, the positive electrode sheet, the upper separator, the negative electrode sheet and the lower separator are stacked in order, wound with a winding needle to form an independent bare battery cell, and fixed with finishing glue.

[0109] In some embodiments, the upper diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. The lower diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. In some embodiments, the thickness of the upper isolation film and / or the lower diaphragm is 5μm to 500μm, specifically 5μm, 100μm, 200μm, 300μm, 400μm, 500μm or any value therebetween.

[0110] In a second aspect, the embodiments of the present application further provide an energy storage battery cell, which can be prepared by the preparation method provided in the above embodiments.

[0111] In the embodiment of the present application, the energy storage battery cell includes a positive electrode sheet coated with a positive electrode material, the positive electrode material includes a lithium manganate matrix, and Bi in-situ grown on the lithium manganate matrix. x M y O z , wherein x, y, z>0, M includes at least one of molybdenum, tungsten and vanadium; in the positive electrode material, the molar amount of the lithium manganate matrix is ​​n3, Bi x M y O z The molar amount of the M element is n2, n2:n3=1:(100~200), and the specific ratio of n2 to n3 can be 1:100, 1:120, 1:140, 1:160, 1:180, 1:200 or any value therebetween.

[0112] Bi x M y O z It belongs to Aurivillius compound, which has excellent high temperature oxidation resistance and structural stability. x M y O z Compounding with lithium manganese oxide can improve the high temperature performance and cycle performance of the positive electrode material; and because this type of compound has holes, compounding it with lithium manganese oxide is also beneficial to improve the electron mobility of the positive electrode material, thereby improving the rate performance of the positive electrode material. In addition, the improvement in the cycle performance of the positive electrode material is also due to Bi x M y O z The unique morphology, specifically: due to Bi x M y O z It is a granular particle with a particle size smaller than that of lithium manganate, which is easy to insert between lithium manganate particles. x M y O zIt is in the shape of flower-shaped microspheres with wrinkles / pores on the surface, which can be tightly combined with lithium manganese oxide particles. It can not only improve the overall compaction density of the positive electrode material, but also improve the structural stability of the lithium manganese oxide material, thereby further improving the cycle performance of the positive electrode material.

[0113] In some embodiments, the positive electrode material Bi x M y O z The molar amount is n7, n7:n3=1:(50~100), and the specific ratio of n7 to n3 can be 1:50, 1:60, 1:70, 1:80, 1:90, 1:100 or any value therebetween.

[0114] In the embodiment of the present application, further, in the positive electrode material, the Bi element part combines with the acid radical ion of the M element to form Bi x-m M y O z , and the other part is deposited on Bi x-m M y O z Above, 0<m<x.

[0115] In the embodiment of the present application, the chemical formula of the positive electrode material can be expressed as: Bi-Bi x-m M y O z / LiMn2O4, the composition of the positive electrode material can be observed by scanning electron microscopy.

[0116] Since bismuth atoms and bismuth molybdate are in the same family, there is an interfacial chemical reaction between the bismuth atoms deposited on bismuth molybdate and bismuth molybdate, which can enhance the bonding tightness between bismuth molybdate particles, thereby further enhancing the structural stability of the positive electrode material, and even further enhancing the cycle performance of the positive electrode material.

[0117] In some embodiments, Bi x-m M y O z Includes a combination of one or more of Bi2MoO6, Bi2MoO6 and BiVO4.

[0118] In the embodiment of the present application, further, in the positive electrode material, Bi x-m M y O z The molar mass is n5, deposited on Bi x- m M y O zThe molar amount of Bi element is n6, n6:n5=(0.1~0.2):1, and the specific ratio of n6 to n5 can be 0.1:1, 0.15:1, 0.2:1 or any value therebetween.

[0119] The ratio of n6 to n5 is too high, which is not conducive to the in situ growth of bismuth molybdate on the surface of lithium manganese oxide; the ratio of n6 to n5 is too low, that is, too few bismuth atoms are deposited on bismuth molybdate, and the bismuth atoms deposited on bismuth molybdate are difficult to effectively improve the structural stability of the positive electrode material.

[0120] In some embodiments, the compacted density of the positive electrode material is 3.06 g / cm 3 ~3.22g / cm 3 , specifically 3.06 g / cm 3 , 3.10 g / cm 3 、3.14 g / cm 3 、3.18 g / cm 3 、3.22g / cm 3 or any value in between.

[0121] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments.

[0122] Example 1

[0123] (1) Weigh 2.0 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 750°C in air atmosphere for 16 h, and obtain lithium manganate after cooling.

[0124] (2) Weigh 0.0205 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, to prepare bismuth salt solution and molybdenum salt solution. Add 1 mmol of hexadecyltrimethylammonium bromide (CTAB) and 1 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0125] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.05:1:100).

[0126] (4) The mixed solution was transferred into a high pressure reactor and heated at 160° C. for 20 h to obtain a reaction product.

[0127] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0128] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganese oxide (LiMn2O4) composite material.

[0129] Example 2

[0130] (1) Weigh 2.1 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 800°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0131] (2) Weigh 0.021 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, to prepare bismuth salt solution and molybdenum salt solution, add 1 mmol of hexadecyltrimethylammonium bromide (CTAB) and 1 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0132] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.1:1:100).

[0133] (4) The mixed solution was transferred to a high-pressure reactor and heated at 160° C. for 20 h to obtain a reaction product.

[0134] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0135] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganese oxide (LiMn2O4) composite material.

[0136] Example 3

[0137] (1) Weigh 2.2 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 850°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0138] (2) Weigh 0.0215 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, to prepare bismuth salt solution and molybdenum salt solution. Add 1 mmol of hexadecyltrimethylammonium bromide (CTAB) and 2 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0139] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1.2 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.15:1:120).

[0140] (4) The mixed solution was transferred to a high-pressure reactor and heated at 170° C. for 16 h to obtain a reaction product.

[0141] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0142] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganese oxide (LiMn2O4) composite material.

[0143] Example 4

[0144] (1) Weigh 2.3 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 900°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0145] (2) Weigh 0.022 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, to prepare bismuth salt solution and molybdenum salt solution, add 2 mmol of hexadecyltrimethylammonium bromide (CTAB) and 2 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0146] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1.5 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.2:1:150).

[0147] (4) The mixed solution was transferred to a high-pressure reactor and heated at 180° C. for 12 h to obtain a reaction product.

[0148] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0149] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganate composite material.

[0150] Example 5

[0151] (1) Weigh 2.2 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 900°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0152] (2) Weigh 0.0210 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, prepare bismuth salt solution and molybdenum salt solution, add 2 mmol of hexadecyltrimethylammonium bromide (CTAB) and 1 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 3 with dilute nitric acid.

[0153] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1.5 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.15:1:150).

[0154] (4) The mixed solution was transferred to a high-pressure reactor and heated at 180° C. for 16 h to obtain a reaction product.

[0155] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0156] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganate composite material.

[0157] Example 6

[0158] (1) Weigh 2.2 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 850°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0159] (2) Weigh 0.0215 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, prepare bismuth salt solution and molybdenum salt solution, add 1 mmol of hexadecyltrimethylammonium bromide (CTAB) and 2 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0160] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1.2 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.15:1:120).

[0161] (4) The mixed solution was transferred to a high-pressure reactor and heated at 170° C. for 18 h to obtain a reaction product.

[0162] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0163] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganate composite material.

[0164] Example 7

[0165] (1) Weigh 2.2 mol of lithium carbonate (Li2CO3) and 4.0 mol of manganese tetraoxide (Mn3O4) respectively and mix them evenly; calcine the mixed powder at 900°C in air atmosphere for 12 h, and obtain lithium manganate after cooling.

[0166] (2) Weigh 0.021 mol of bismuth nitrate pentahydrate Bi(NO3)3·5H2O and 0.01 mol of sodium molybdate dihydrate Na2MoO4·2H2O as bismuth source and molybdenum source, respectively, prepare bismuth salt solution and molybdenum salt solution, add 2 mmol of hexadecyltrimethylammonium bromide (CTAB) and 2 mmol of bismuth oxide (Bi2O3) to the bismuth salt solution, and adjust the pH of the solution to 4 with dilute nitric acid.

[0167] (3) The bismuth salt solution and the molybdenum salt solution were mixed and dispersed for 1 hour, and then 1.8 mol of the prepared lithium manganate powder was added and stirred for 1 hour to obtain a mixed solution (in the mixed solution, n1:n2:n3=2.1:1:180).

[0168] (4) The mixed solution was transferred to a high pressure reactor and heated at 180° C. for 18 h to obtain a reaction product.

[0169] (5) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol.

[0170] (6) The product after centrifugal washing is dried in a vacuum drying oven at 80° C. for 12 h, and ground for later use after cooling to obtain a positive electrode material, which is an in-situ grown bismuth molybdate (Bi-Bi2MoO6) / lithium manganate composite material.

[0171] Example 8

[0172] Compared with Example 1, the difference is:

[0173] In step (3), the amount of the prepared lithium manganate powder added is 2 mol, and in the mixed solution, n1:n2:n3=2.05:1:200.

[0174] In step (4), the heating temperature of the mixed solution in the high-pressure reactor is 140°C.

[0175] Example 9

[0176] Compared with Example 1, the difference is:

[0177] In step (2), 0.01 mol of the molybdenum source is replaced by 0.01 mol of a tungsten source, and the selected tungsten source is sodium tungstate dihydrate Na2WO4·2H2O.

[0178] Example 10

[0179] Compared with Example 1, the difference is:

[0180] In step (2), 0.01 mol of molybdenum source is replaced by 0.0195 mol of vanadium source, and the selected vanadium source is NaVO4;

[0181] In step (3), in the mixed solution, n1:n2:n3=1.05:1:100.

[0182] Embodiment 11

[0183] Compared with Example 1, the difference is:

[0184] In step (2), bismuth oxide is not added to the bismuth salt solution.

[0185] Example 12

[0186] Compared with Example 1, the difference is:

[0187] In step (2), CTAB is not added to the bismuth salt.

[0188] Comparative Example 1

[0189] The lithium manganese oxide prepared in step (1) of Example 1 was used as the positive electrode material.

[0190] Comparative Example 2

[0191] The difference from Example 1 is the steps after step (2):

[0192] (3) The bismuth salt solution and the molybdenum salt solution are mixed, dispersed for 1 hour, and then heated in a high-pressure reactor at 180° C. for 12 hours to obtain a reaction product.

[0193] (4) After the reaction product is cooled to room temperature, it is centrifuged and washed alternately with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven at 80° C. for 12 h. After cooling, it is ground for later use to obtain bismuth molybdate powder.

[0194] (5) Add 1 mol of the prepared lithium manganese oxide powder to the above bismuth molybdate powder and mix them evenly to obtain a positive electrode material. The positive electrode material is a mixture of bismuth molybdate and lithium manganese oxide physically mixed.

[0195] Comparative Example 3

[0196] The difference from Example 1 is that:

[0197] In step (3), the molar amount of the prepared lithium manganate powder added is 0.1 mol, and in the obtained mixed solution, n1:n2:n3=2.05:1:10.

[0198] Comparative Example 4

[0199] The difference from Example 1 is that:

[0200] In step (3), the molar amount of the prepared lithium manganate powder added is 5 mol, and in the obtained mixed solution, n1:n2:n3=2.05:1:500.

[0201] The performance of the positive electrode materials prepared in the above-mentioned Examples 1-12 and Comparative Examples 1-4 was tested, and the testing method was as follows:

[0202] 1. Compaction density test:

[0203] The compaction density tester of the positive electrode material was used to test the compaction performance of the positive electrode material. 1g of the positive electrode material was processed and compacted under a pressure of 3t for 30s to obtain the compaction data of the material. The compaction density was > 3 g / cm 3 .

[0204] 2. Power-off performance test:

[0205] Take 0.8g of positive electrode material, 0.1g of conductive carbon black, and 0.1g of polyvinylidene fluoride and put them into a ball mill, add 15ml of N-methylpyrrolidone, ball mill to form a uniform slurry, then evenly coat it on aluminum foil, and vacuum dry it at 110°C for 12h to obtain a positive electrode. Cut the dried electrode into a disc with a diameter of 15mm, which is the positive electrode. In the glove box, assemble and seal the negative electrode shell, spring, gasket, negative electrode sheet, diaphragm (Celgard PP / PE / PP three-layer composite film), electrolyte (EC / DMC / EMC volume ratio 1:1:1, LiPF6 concentration is 1mol / L), positive electrode sheet, and positive electrode shell to obtain a button battery and let it stand for 24h. The obtained battery was then placed in a constant temperature box for testing. The battery was discharged to 2.0V at a current density of 1C. After standing for 2 minutes, it was charged to 4.2V at a current density of 1C. The above steps were repeated for 200 cycles to obtain the cycle retention rate.

[0206] The LAND battery testing system was used to conduct discharge capacity (0.1C / 0.5C / 1C) and first-cycle charge and discharge efficiency performance tests at 25°C and 3.0 V to 4.3 V. The reference capacity was set to 200 mA / g, and 1C corresponded to a current density of 200 mA / g.

[0207] The test results of the positive electrode materials prepared in Examples 1-12 and Comparative Examples 1-4 are shown in Table 1 below:

[0208] Table 1

[0209]

[0210] In the above Table 1:

[0211] "0.1C gram capacity" refers to the amount of electricity that a battery can release when it is discharged at a discharge rate of 0.1C.

[0212] "First efficiency" refers to the ratio of the capacity released after the battery is fully charged for the first time to the capacity when it is fully charged for the first time.

[0213] "200-week capacity retention rate" refers to the percentage value obtained by comparing the battery capacity after it is fully charged and the capacity when it is fully charged for the first time after the battery has been used for 200 charge and discharge cycles.

[0214] "Capacity recovery rate after full charge and storage at 60℃ for 48 hours" means: after the battery is fully charged, stored at 60℃ for 48 hours, and then fully charged and discharged, the ratio of the discharge capacity to the initial capacity of the battery is the capacity recovery rate after full charge and storage at 60℃ for 48 hours.

[0215] In the above Table 1, by analyzing Examples 1-12 and Comparative Examples 1-4, it can be concluded that the use of appropriate amounts of molybdenum acid salts and bismuth salts to modify the lithium manganese oxide positive electrode material can improve the compaction density, high temperature performance and cycle performance of the positive electrode material.

[0216] Specifically, by comparing Example 1 with Comparative Example 1, it can be concluded that the use of molybdenum acid salts and bismuth salts to modify the lithium manganese oxide positive electrode material can effectively improve the high temperature performance and cycle performance of the positive electrode material.

[0217] By comparing Example 1 with Comparative Example 2, it can be concluded that although the physical mixing of molybdenum acid salts and bismuth salts with lithium manganate positive electrode materials can improve the compaction density of the positive electrode materials to a certain extent, it cannot improve the defects of the positive electrode materials in lithium ion battery applications. By in-situ generation of molybdenum acid bismuth by molybdenum acid salts and bismuth salts on the surface of lithium manganate positive electrode materials, the structural stability of the positive electrode materials can be improved, thereby effectively improving the capacity retention rate and capacity recovery rate of the positive electrode materials, that is, improving the high temperature performance and cycle performance of the positive electrode materials.

[0218] By comparing Example 1 with Comparative Example 3, it can be concluded that the content of lithium manganese oxide in the positive electrode material is too low, that is, the content of bismuth molybdenum acid is too high, and the compaction density, gram capacity, first efficiency, high temperature performance and cycle performance of the positive electrode material will be affected.

[0219] By comparing Example 1 with Comparative Example 4, it can be concluded that the content of lithium manganese oxide in the positive electrode material is too high, that is, the content of bismuth molybdenum acid is too low, and the modification effect of bismuth molybdenum acid on the lithium manganese oxide material is not obvious, which is not conducive to improving the high temperature performance and cycle performance of the positive electrode material.

[0220] Comparing Example 1 with Example 11, it can be concluded that the bismuth atoms deposited on the bismuth molybdenum acid can improve the bonding tightness between the bismuth molybdenum acid (formed by the reaction of molybdenum acid salt and bismuth salt) particles, which is beneficial to the improvement of the cycle performance of the positive electrode material. The reason is that the bismuth atoms in bismuth oxide are of the same series as bismuth molybdate. After the bismuth atoms in bismuth oxide are deposited on the surface of bismuth molybdate, there is an interfacial chemical reaction between them and bismuth molybdate, which can improve the bonding tightness between the bismuth molybdate particles, thereby further improving the structural stability of the positive electrode material, and then improving the capacity recovery rate of the positive electrode material when stored at 60°C for 48 hours at full charge, that is, the cycle performance of the positive electrode material is improved.

[0221] By comparing Example 1 with Example 12, it can be concluded that the addition of an appropriate amount of surfactant can improve the bonding tightness between bismuth molybdenum acid (generated by the reaction of molybdenum acid salt and bismuth salt) and lithium manganese oxide, so that the compaction density of the positive electrode material is improved; and the addition of the surfactant makes the microscopic morphology of bismuth molybdenum acid better, and its specific surface area and porosity are increased, which is conducive to the close bonding of lithium manganese oxide and the bismuth molybdenum acid generated in situ on its surface, which is conducive to improving the structural stability of the positive electrode material, thereby making the volume expansion of the positive electrode material at high temperature smaller, the capacity recovery rate of fully charged 60°C storage for 48 hours is higher, and its high temperature adaptability is improved.

[0222] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an energy storage battery cell, characterized in that: The method comprises preparing a positive electrode material, wherein the steps of preparing the positive electrode material include: A mixed solution containing lithium manganate, bismuth salt and molybdate acid salt is prepared, wherein the molybdate acid salt includes at least one of molybdate, tungstate and vanadate, wherein the molar amount of bismuth ions in the mixed solution is n1, the total molar amount of molybdate ions, tungstate ions and vanadate ions is n2, the molar amount of lithium manganate is n3, and n1:n2:n3=(1.05-2.2):1:(100-200); The mixed solution is subjected to a solvothermal reaction treatment to obtain a positive electrode material.

2. The preparation method according to claim 1, characterized in that The mixed solution also contains bismuth oxide, and the molar amount of bismuth oxide in the mixed solution is n4, n4:n2=(0.1-0.2):

1.

3. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction treatment is 140° C. to 200° C., and the time of the solvent thermal reaction treatment is 12 h to 24 h.

4. The preparation method according to claim 1, characterized in that: The mixed solution also contains 1 mmol to 2 mmol of a surfactant, which is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and hexadecylpentyldimethylammonium bromide.

5. The preparation method according to claim 1, characterized in that: The pH of the mixed solution is 1-5.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation of the mixed solution containing lithium manganate, bismuth salt and molybdenum acid salt comprises the steps of: uniformly mixing the bismuth salt solution, the molybdenum acid salt solution and the lithium manganate; Before the bismuth salt solution, the molybdate acid salt solution and the lithium manganate are uniformly mixed, the preparation method further comprises the following steps: Preparation of the lithium manganate: uniformly mixing a lithium source and a manganese source, wherein the molar ratio of lithium ions in the lithium source to manganese ions in the manganese source is (1-1.2):3, to obtain a manganese-lithium mixture, and then calcining the manganese-lithium mixture at 750° C. to 900° C. to obtain lithium manganate; and / or, preparing the bismuth salt solution: mixing a bismuth source with a first solvent to prepare a first prepared solution, and adding a surfactant and bismuth oxide to the first prepared solution to obtain a bismuth salt solution; and / or, The molybdenum acid salt solution is prepared by mixing a molybdenum source with a second solvent to prepare a second prepared solution, wherein the molybdenum source includes at least one of a molybdenum source, a tungsten source and a vanadium source, to obtain a molybdenum acid salt solution.

7. The preparation method according to claim 6, characterized in that: The preparation method further comprises at least one of the following features (1) to (8): (1) After adding a surfactant and bismuth oxide to the first prepared solution, the preparation method further comprises adjusting the first prepared solution to be acidic; (2) The bismuth source includes bismuth nitrate pentahydrate; (3) After the molybdenum source and the second solvent are mixed to prepare the second prepared solution, the preparation method further comprises adjusting the second prepared solution to be acidic; (4) The molybdenum source includes sodium molybdate dihydrate; (5) The tungsten source includes sodium tungstate dihydrate; (6) The vanadium source includes sodium vanadate; (7) the first solvent and the second solvent are independently selected from at least one of water, ethanol and ethylene glycol; (8) The concentration of the first prepared solution and / or the second prepared solution is ≥ 0.1 mol / L.

8. An energy storage battery cell, prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The energy storage battery cell comprises a positive electrode sheet coated with a positive electrode material, wherein the positive electrode material comprises a lithium manganate matrix and Bi in-situ grown on the lithium manganate matrix. x M y O z , wherein x, y, z>0, and M includes at least one of molybdenum, tungsten and vanadium; In the positive electrode material, the molar amount of lithium manganate matrix is ​​n3, Bi x M y O z The molar amount of element M is n2, n2:n3=1:(100~200).

9. The energy storage cell according to claim 8, characterized in that: In the positive electrode material, the Bi element partially combines with the acid radical ion of the M element to form Bi x-m M y O z , and the other part is deposited on Bi x-m M y O z Above, 0<m<x.

10. The energy storage cell according to claim 9, characterized in that: In the positive electrode material, Bi x-m M y O z The molar mass is n5, deposited on Bi x-m M y O z The molar amount of Bi element is n6, n6:n5=(0.1~0.2):1.

Citation Information

Patent Citations

  • Bismuth tungstate-coated lithium iron phosphate positive electrode material and preparation method thereof

    CN113471420A

  • Hydrangea-shaped bismuth vanadate-MXene heterojunction as well as preparation method and application thereof

    CN116553550A